erdahermwan@gmail.com - Erda Hermawan; Ahmad Mulyadi; Sri Rahayu (Jurnal Sains Pertanian Equator, 2020)
ABSTRACTInformation about the stock of mangrove crabs (Scylla tranquebarica) in West Kalimantan is still very minimal, especially in Kubu Village, Kubu District. The purpose of this study is to estimate the stock of S. tranquebarica the catch of the fishermen from the Village of Kubu sub-District, Kubu Kubu Raya District of West Kalimantan Province. The method used for sampling was the Census method in which the samples to be observed were all the catch of mangrove crabs in 2 (two) collectors in Kubu Village. Sampling of S. tranquebarica was carried out at once time interval in biweekly for 4 (four) months. This study was conducted in September-December 2018. Based on the results of the study, S. tranquebarica which was caught during the study were 413 crabs, in which male crabs were caught of 301 crabs and female crabs of 112 crabs. The distribution of the frequency width of the carapace of male crabs observed ranges from 95-60 mm with a weight of 185-1279 grams, while the females range from 100 to 150 mm and the weight of the 214-962 grams. The relationship of the width and the weight of S. tranquebarica male is allometrik positive, the female is isometric. The width of the asimptotik (L∞) S. tranquebarica males 242 mm, females 165 mm, coefficient of growth (K) male 0.15 per year, the female 0,39 per year. The natural mortality of males 0.236 females 0.492 male arrest mortality of 0.421 females 0.483. The exploitation rate of male crabs is 0.640 per year while females are 0.495 annually which means that males crabs have been over-exploited while females have not been over-exploited. Keywords: Stock estimation, Scylla tranquebarica, Width and weight relationship